2008
DOI: 10.1007/s10549-008-0196-x
|View full text |Cite
|
Sign up to set email alerts
|

Green tea catechins inhibit angiogenesis through suppression of STAT3 activation

Abstract: Previous studies indicate that green tea extract may inhibit breast cancer progression by blocking angiogenesis, although the molecular mechanisms are not well defined. We demonstrate that administration of Polyphenon E (Poly E), a standardized green tea extract, inhibited MDA-MB231 breast cancer and human dermal microvascular endothelial (HMVEC) cell migration and the expression of vascular endothelial growth factor (VEGF) and matrix metalloproteinase 9 (MMP9). In addition, Poly E inhibited VEGF-induced neova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…GTE treatment was well tolerated, although higher doses increased insomnia and nervousness (albeit without grade 4 toxicities). This study also provided some very important biomarker data, including data on VEGF that are consistent with previously reported effects of GTE (18,31). Baseline stromal VEGF levels correlated with clinical (P = 0.04) but not histologic response.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…GTE treatment was well tolerated, although higher doses increased insomnia and nervousness (albeit without grade 4 toxicities). This study also provided some very important biomarker data, including data on VEGF that are consistent with previously reported effects of GTE (18,31). Baseline stromal VEGF levels correlated with clinical (P = 0.04) but not histologic response.…”
supporting
confidence: 85%
“…Green tea polyphenols inhibit the angiogenesis of breast cancer cells by inhibiting the expression of VEGF and MMP-9 through suppressing signal transducers and activators of transcription-3 activation (17,18). EGCG also inhibited cell viability, capillary tube formation, and migration of human umbilical vein endothelial cells and inhibited angiogenic and metastasis markers (VEGF, CD31, MMP-2, MMP-7, MMP-9, and MMP-12) in a xenograft model of pancreatic cancer (19).…”
mentioning
confidence: 98%
“…1B). To exclude the nonspecific effect that may be caused by the ␣ 1 -antichymotrypsin reporter gene, the same experiments were performed by using other STAT3-responsive luciferase reporter constructs of GAS (IFN-␥-activating sequence) reporter and m67 reporter (a synthetic STAT3-responsive promoter) (31,32), and the results showed that CUEDC2 also inhibits the expression of these two reporters in a dose-dependent manner ( . 24 h after transfection cells were stimulated by IFN-␣ (50 ng/ml) for the indicate periods, and total cell lysates were immunoblotted using anti-p-STAT3 (Tyr-705), anti-FLAG and anti-HA antibodies.…”
Section: Cuedc2 Inhibits Stat3 Transcriptional Activity-cuedc2mentioning
confidence: 99%
“…Accumulating evidence supports a pivotal role of constitutively activated STAT3 in tumor angiogenesis [11]. In a wide range of cancers, including breast cancer, gastric cancer, head and neck cancer, pancreatic cancer, and melanoma, immunohistochemical studies have indicated that angiogenesis is directly correlated with constitutively elevated STAT3 activity [12][13][14][15]. Not surprisingly, angiogenesis is a complex multistage process and is regulated by the balance between angiogenesis and angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%